Kesiapan Multi-Tiered System of Supports (MTSS) dalam Layanan BK untuk Merespons Dinamika Sosial Budaya Siswa: Studi Observasional di SMKN Manonjaya dan SMAN 8 Tasikmalaya - Siti Nur Aini Putri; Feida Noorlaila Istiadah; Mutiara Hardini; Naylla Dinarros; Salwa Destriani (Yayasan Literasi Sains Indonesia, 2026)
This study aims to describe the implementation of Guidance and Counseling (BK) services based on the Multi-Tiered System of Support (MTSS) in secondary schools. The research was conducted through observational activities at SMK Negeri Manonjaya and SMA Negeri 8 Tasikmalaya. The method used was a qualitative descriptive approach, with data collected through direct observation, semi-structured interviews, MTSS checklist instruments, and documentation. The results show that the implementation of BK services at the observed schools has been carried out well across all MTSS tiers. Tier 1 services (universal prevention) were implemented through classical guidance, counseling socialization, and preventive education such as bullying prevention. Tier 2 services (targeted intervention) focused on identifying at-risk students and providing group guidance and coordination with homeroom teachers and parents. Tier 3 services (intensive intervention) included scheduled individual counseling, in-depth assessments, and case documentation. Although some constraints were identified, such as limited facilities and the large number of students, overall BK services demonstrated professional performance and strong collaboration among school stakeholders. This study concludes that the MTSS-based BK service system has been implemented effectively and can serve as a foundation for further development.